Analisis Evaluasi Penerapan Pemungutan Pajak Air Tanah Dalam Upaya Peningkatan Pendapatan Pajak Air Tanah Di BAPENDA Kota Bekasi (Studi Kasus BAPENDA Kota Bekasi) - Maria Magdalena Ika; Dian Wahyudin (Jurnal Ilmu Administrasi Publik, 2021)
This study was conducted to determine the analysis of the  application  of  groundwater  tax  collection  as  an effort to increase groundwater tax revenue in the BAPENDA (Regional Revenue Agency) of Bekasi City, the   obstacles   that   arise   in   the   groundwater   tax collection and the efforts made to overcome them. This study used a descriptive qualitative research method. Data was collected through interviews, observation and documentation. The results of the study show that data collection and monitoring of groundwater tax collection as an effort to increase groundwater tax revenue at the BAPENDA of Bekasi City is practically in accordance with Law No. 28 of 2009 and regulations regarding groundwater tax. However, the ineffectiveness of the tax collection system and the lack of maximum groundwater tax services have made groundwater tax collection at the BAPENDA of Bekasi City less  than optimal.